The potential functions of HvDJ genes in regulating salt tolerance in barley - Xu, Yunfeng; Sun, Haoran; Shen, Ling; Wan, Boyan; Liu, Lijun; Zhang, Guoping; Shen, Qiufang (Frontiers in Plant Science, 2025)
The important roles of JDP members in regulating abiotic and biotic stress tolerance have been demonstrated in many plants. However, fewer studies have explored the JDP gene family and its role in the salt stress response in barley, a crop known for its superior salt tolerance compared to other major cereals. Here, we identified a total of 109 putative JDP genes (nine HvDJAs, eight HvDJBs, 92 HvDJCs) in barley. Promoter analysis of HvDJs suggested that HvDJs might be involved in the processes of hormone regulation and stress response. Tandem and segmental duplications appear to be the driving forces behind JDP gene family expansion. RNA-seq analysis showed that the expression of 37 HvDJs was salt-induced, and HvDJB06, HvDJC58, and HvDJC59 were the most differentially expressed under salt stress. Protein–protein interaction analysis indicated that HvDJA09 and HvDJA05 play core roles in the complex regulatory network. Taken together, the current study provides valuable information for a deeper understanding of the function of HvDJs in regulating salt stress tolerance in barley.